A survey in traditional information retrieval models - Dong, Hai; Hussain, Farookh Khadeer; Chang, Elizabeth (Institute of Electrical and Electronics Engineers (IEEE), 2008)
As a matter of fact, many so-called semantic search algorithms are derived friom the traditional index-term-based search models. In this paper, we survey the traditional information retrieval models by categorizing them into three main classes and eleven subclasses, and analyse their benefits and issues of them.